The Influence of Ownership Structure, Debt Structure, and Independent Commissioner on Earning Management - Muhammad Yanuarsa; Dwi Marlina Wijayanti; Slamet Haryono (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2021)
This study aims to examine the effect of independent commissioners, blockholder ownership, long-term debt, short-term debt, institutional ownership, family ownership, and managerial ownership on earnings management. This study is a quantitative study with a sample of 71 companies listed on the Indonesia Stock Exchange in 2017-2019. The data is processed by multiple regression using E-views. The results show that long-term debt has a negative effect on earnings management and short-term debt has a positive effect on earnings management. Other results show that independent board of commissioners, blockholder ownership, institutional ownership, family ownership, and managerial ownership do not cause earnings management. The limitation of this study is that it does not use a sample in the financial sector. Nevertheless, this research contributes practically and theoretically. This study also facilitates the weaknesses of previous research by adding variables of debt structure and ownership structure.